Demographics and Interest Rates in Asia - Arslanalp, Serkan (IMF Working Papers; Working Paper ;, 2018)
Demographic developments have been regarded as one important cause of the long-term movement in global interest rates. This paper provides empirical evidence of the relationship between demographics and interest rates over a wide sample of advanced and emerging market economies. It also finds that capital account openness limits the direct sensitivity of a country's interest rates to its own demographics. The results suggest that future demographic developments will continue to apply downward pressure on the interest rates in Asia which foresees a rapid aging.